2005
DOI: 10.1002/jcp.20288
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal SH3 domain of CrkII regulates the assembly and function of the DOCK180/ELMO Rac‐GEF

Abstract: Genetic studies in Caenorhabditis elegans identified an evolutionarily conserved CED-2 (CrkII), CED-5 (DOCK180), CED-12 (ELMO), CED-10 (Rac1) module important for cell migration and phagocytosis of apoptotic cells. Previous studies have shown that DOCK180 and ELMO comprise an unconventional bipartite Dbl homology domain-independent Rac guanine nucleotide exchange factor (Rac-GEF); but it is still unclear how CrkII functions in Rac-GEF activity. In this study, we have characterized a unique function of CrkII in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…However, we could not exclude the possibility that CrkII is required for the regulation of cell migration by RhoG, because Dock180⌬N-ISP, which is a large protein with multiple regions, might function as a dominantnegative protein towards CrkII for other reasons. The relationship between the p130Cas-Crk-Dock180 and the RhoG-ELMO-Dock180 pathways in the regulation of cell migration remains unclear, but a recent study reported that the C-terminal second SH3 domain of CrkII regulates the interaction between RhoG and ELMO (Akakura et al, 2005). Further studies are required for elucidating the precise mechanisms for the regulation of cell migration mediated by Dock180-dependent activation of Rac.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not exclude the possibility that CrkII is required for the regulation of cell migration by RhoG, because Dock180⌬N-ISP, which is a large protein with multiple regions, might function as a dominantnegative protein towards CrkII for other reasons. The relationship between the p130Cas-Crk-Dock180 and the RhoG-ELMO-Dock180 pathways in the regulation of cell migration remains unclear, but a recent study reported that the C-terminal second SH3 domain of CrkII regulates the interaction between RhoG and ELMO (Akakura et al, 2005). Further studies are required for elucidating the precise mechanisms for the regulation of cell migration mediated by Dock180-dependent activation of Rac.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway may mediate integrin-induced Rac activation, cell migration, phagocytosis and nerve growth factor (NGF)-induced neurite outgrowth Grimsley et al, 2004;Katoh and Negishi, 2003). The RhoG and Crk pathways might be connected, since Crk, Dock180 and ELMO can form a ternary complex (Gumienny et al, 2001;Wu et al, 2001), and CRK might regulate interactions between Dock180, ELMO, Rac and RhoG (Akakura et al, 2005).…”
Section: Engulfmentmentioning
confidence: 99%
“…GTP-loaded) MIG-2 regulates corpse removal by modulating plasma membrane recruitment of the unconventional bipartite CED-5 (Dock180)-CED-12 (Elmo) GEF complex (Gumienny et al, 2001;Wu and Horvitz, 1998a). The GEF complex is stabilized further by the adaptor molecule CED-2 (CrkII), which also promotes the activation of CED-10 (Akakura et al, 2005;Gumienny et al, 2001). GTP-bound CED-10 initiates extensive cytoskeletal rearrangements, a requirement for the engulfment of cell corpses (Kiyokawa et al, 1998;Reddien and Horvitz, 2000).…”
Section: Introductionmentioning
confidence: 99%